Long-latency TMS-evoked potentials during motor execution and inhibition - Yamanaka, Kentaro; Kadota, Hiroshi; Nozaki, Daichi (Frontiers in Human Neuroscience, 2013)
Transcranial magnetic stimulation (TMS) has often been used in conjunction with electroencephalography (EEG), which is effective for the direct demonstration of cortical reactivity and corticocortical connectivity during cognitive tasks through the spatio-temporal pattern of long-latency TMS-evoked potentials (TEPs). However, it remains unclear what pattern is associated with the inhibition of a planned motor response. Therefore, we performed TMS-EEG recording during a go/stop task, in which participants were instructed to click a computer mouse with a right index finger when an indicator that was moving with a constant velocity reached a target (go trial) or to avoid the click when the indicator randomly stopped just before it reached the target (stop trial). Single-pulse TMS to the left (contralateral) or right (ipsilateral) motor cortex was applied 500 ms before or just at the target time. TEPs related to motor execution and inhibition were obtained by subtractions between averaged EEG waveforms with and without TMS. As a result, in TEPs induced by both contralateral and ipsilateral TMS, small oscillations were followed by a prominent negative deflection around the TMS site peaking at approximately 100 ms post-TMS (N100), and a less pronounced later positive component (LPC) over the broad areas that was centered at the midline-central site in both go and stop trials. However, compared to the pattern in go and stop trials with TMS at 500 ms before the target time, N100 and LPC were differently modulated in the go and stop trials with TMS just at the target time. The amplitudes of both N100 and LPC decreased in go trials, while the amplitude of LPC decreased and the latency of LPC was delayed in both go and stop trials. These results suggested that TMS-induced neuronal reactions in the motor cortex and subsequent their propagation to surrounding cortical areas might change functionally according to task demand when executing and inhibiting a motor response.